Integrating urban design principles in promoting sports tourism for Bukit Jalil sports complex, Kuala Lumpur, Malaysia - Mohebbi, Roshanak (2014)
Globally, it is evident that there is a growing effort by urban managers to strengthen the relationship between sports and the urban environment. This has shaped the recent phenomenon of “urban sports tourism” to change the image of cities worldwide. The phenomenon has emphasized the aspects of sport and tourism to differentiate from other tourism attractions. However, in managing urban sports tourism little is discussed about the roles of urban design principles in making sports complexes as attractive and sustainable tourism destinations. This study aims to understand how urban design principles can be integrated in promoting urban sport tourism in sports complexes. The theoretical framework was based on joint theories of urban design and sports tourism to formulate the urban design principles for global urban sports tourism destinations. Three principles that affect the promotion of sports tourism the most are accessibility, legibility and diversity. Afterwards, the research employed the qualitative method using a case study approach. It triangulates two techniques, which include field observation and in-depth interviews. Field observation was conducted to evaluate the existing urban design principles of Bukit Jalil Sports Complex (BJSC), as one of the large-scale sports complexes in the city of Kuala Lumpur, Malaysia. By using photographs, it enables the researcher to obtain a clear picture of the actual condition of the sports complex and urban design principles that influence its usage as a centre for sporting facilities. In-depth interviews with key persons including government and sports tourism association were conducted to identify the urban design issues and strategies relating to urban sports tourism for the city of Kuala Lumpur,Malaysia. The results from field observation indicate that despite the existence of public transportation, various landmarks and indoor sport activities at BJSC, further improvements are needed in terms of pedestrian design, eradication of abandoned spaces and integration of various activities and functions with the place based on the needs of sports tourism. In addition, the interview analysis has identified three themes – planning and design, sports facilities attributes, and activities and events – that promote urban sports tourism and which also can be related to the sustainability factors in terms of environmental, economic and social, respectively. The study adds to our understanding of the success of a sports complex in attracting sports tourists by integrating urban design principles in the development proposal. Thus, the sports complex itself can act as a socio-economic catalyst to increase the diversity of tourism attractions towards enhancing the development of the tourism industry in Malaysia.